1991
DOI: 10.1111/j.1365-2044.1991.tb09362.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyolysis and operating position

Abstract: SummaryRhabdomyolysis during routine surgery was studied in three groups of patients who had surgery, with limited trauma to muscle, in the lateral and supine positions, and prone on the spinal frame. A range of blood tests was performed (before surgery, and on the jirst, third and seventh day after operation). These showed that a creatine kinase increase in the 24 hours and the early appearance of myoglobin in the serum were the best indicators. Rhabdomyolysis was associated with the lateral position and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Other positions associated to muscle injury are prone 9,18,19 , lateral 7,14,20 and supine 21 . Long surgical procedures are also major risk factors 7,8,10,14,16,[18][19][20][21] . Most surgery-related rhabdomyolysis are associated to procedures lasting 4 to 11 hours, although critical time above which injuries are established is still to be determined 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Other positions associated to muscle injury are prone 9,18,19 , lateral 7,14,20 and supine 21 . Long surgical procedures are also major risk factors 7,8,10,14,16,[18][19][20][21] . Most surgery-related rhabdomyolysis are associated to procedures lasting 4 to 11 hours, although critical time above which injuries are established is still to be determined 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The early development of rhabdomyolysis is surprising because prolonged immobilization and ischemia longer than 4 hours usually cause hyperkalemia 11 and rhabdomyolysis in the supine position. 2,12 Third, the CPK levels were not elevated when measured postoperatively in our patient. It has been reported that CPK levels are normal or only moderately elevated in zidovudine-induced rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 49%
“…The range of normal values was 30 to 135 IU/L for women and 55 to 177 IU/L for men. One CPK measure was made 12 h before surgery and another 24 h afterwards because the peak of CPK dosage is usually after the potential injury [31,35,36]. RML was defined as an increase of five or more times the superior limit of CPK level [33,34], being respectively, 675 IU/L for women and 850 IU/L for men.…”
Section: Methodsmentioning
confidence: 99%